1996
DOI: 10.1021/ja960421+
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Examination of the Electronic Excited States of Glycylglycine and Other Dipeptides:  Observation of a Carboxylate→Amide Charge Transfer Transition

Abstract: We have examined the UV resonance Raman and the VUV absorption spectra of aqueous glycylglycine and other dipeptides. We observe strong resonance Raman enhancement of the amide I, II, and III bands and the amide CαH bending mode in a manner similar to that we observed previously with excitation within the π→π* transition of N-methylacetamide (Chen, X. G.; Asher, S. A.; Schweitzer-Stenner, R.; Mirkin, N. G.; Krimm, S. J. Am. Chem. Soc. 1995, 117, 2884). However, in addition, we observe strong resonance Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
99
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 55 publications
12
99
0
Order By: Relevance
“…Such a small change of J rules out the possibility that the backbone conformation changes with respect to pH. It is believed that such a strong pH dependency of trialanine CD spectrum is likely related to the charge transfer transitions 41,[64][65][66][67] between the C-terminal carboxylate group and the neighboring peptide group as discussed by Dragomir et al 41 , where they examined the far-UV absorption and electronic CD spectra of Ala-X and X-Ala (where X represents different amino acid residues) and considered the difference spectra obtained by subtracting the spectrum of the cationic species from that of the corresponding zwitterionic one. In Figure 4a inset, the difference CD spectrum of trialanine obtained by subtracting the pH 2 spectrum from the pH 7 spectrum at 208C is plotted.…”
Section: Temperature and Ph Dependencies Of Nà àH Proton Chemical Shimentioning
confidence: 99%
“…Such a small change of J rules out the possibility that the backbone conformation changes with respect to pH. It is believed that such a strong pH dependency of trialanine CD spectrum is likely related to the charge transfer transitions 41,[64][65][66][67] between the C-terminal carboxylate group and the neighboring peptide group as discussed by Dragomir et al 41 , where they examined the far-UV absorption and electronic CD spectra of Ala-X and X-Ala (where X represents different amino acid residues) and considered the difference spectra obtained by subtracting the spectrum of the cationic species from that of the corresponding zwitterionic one. In Figure 4a inset, the difference CD spectrum of trialanine obtained by subtracting the pH 2 spectrum from the pH 7 spectrum at 208C is plotted.…”
Section: Temperature and Ph Dependencies Of Nà àH Proton Chemical Shimentioning
confidence: 99%
“…Chen et al 97 measured the UVRR spectra of several isotopic derivatives of acetylglycine and found that most of the 1400 cm 1 band intensity arises from the COO ss. It is overlaid by another band assignable to CH 2 wagging (w).…”
Section: Uvrr Of Di-and Tripeptidesmentioning
confidence: 99%
“…28 In the same frequency region, the CO 2 symmetric stretch, which exhibits a downshift of 14 cm 1 upon 13 CO 2 substitution, was also resonance enhanced at 1396 cm 1 , when the CO 2 group yields charge transfer (CT) interactions with the amide group. 29 On the other hand, there is an argument that the 1495 cm 1 band is an amide II band of cis peptide linkages, since the band is observed upon the increase of laser power. 30,31 The trans -NHDCO-bond is thought to undergo photoisomerization into cis -NHDCO-upon UV irradiation.…”
Section: Amide Modesmentioning
confidence: 99%